Process Model and Digitalization of the Coal Gas Outburst Prevention - Shao-jie Hou; Yu-wei Zhang; Yuan-ping Cheng (Institute of Advanced Engineering and Science, 2014)
Regional coal gas outburst prevention has become the prerequisite of coal mining in the most China underground collieries. It touched on miners’ lives so closely, but especially lacked of digitalization due to the hostile working environment, sightless strata reserves, complicated and long-time workflow. By synthesizing the vital rules issued by China governments and various techniques of coal gas outburst prevention, we proposed a novel process model for them embodied as a logical workflow. The model consisted of two operation links and two judging nodes, and dealt with three types of data. Then an easy-use and practical process data management software system was developed. By testing in Qinan colliery, the system was proved to be fully considering user experience and helpful to promote digitalization of coal gas outburst prevention. Compared with the traditional management, the digitalization might help engineers identify anomalies more quickly and avoid gas accidents in time. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4240